PENGARUH PENGETAHUAN TERHADAP MINAT MEMILIH PADA PEMILIHAN KEPALA DAERAH - Safaruddin, Safaruddin; Mulyawati, Netari (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2024)
This article was created based on research carried out in order to determine "the influence of public knowledge on interest in electing regional head candidates in the 2024 simultaneous regional head elections (pilkada) (case study of the people of RT.11/RW.01, Sekarjaya sub-district, Baturaja City)". The dependent variable in this research is interest in voting while the independent variable is knowledge. The sample used in this research was 77 (seventy seven) people. This research uses a questionnaire as the main (primary) data, then the data results are analyzed using multiple regression by carrying out a simultaneous test (F), determination test, and partial test (t) with a significance level of 5% (?=0.05) which is processed using the tool is SPSS 23. The results of this research show that there is a simultaneous positive and significant influence on knowledge on people's voting interest in regional elections as seen through the F statistical test with a significance value of 0.000. The results of the t statistical test indicate that Knowledge has a positive and significant effect with a significance level of 0.000.